Future of Green Products in Pakistan: An Empirical Study about Green Purchase Intentions - Rizwan, Muhammad; Asif, Rana Muhammad; Hussain, Sajjad; Asghar, Mubashir; Hassan, Muhammad; Javeed, Umer (Asian Journal of Empirical Research, 2013)
Success of Green products becomes very necessary to keep our earth alive and help the human race to sustain. The purpose of this study is to identify the important factors that influence the green purchase intentions of the people of Pakistan. A self-administered questionnaire technique is use to analyze the green purchase intention of the people. Green purchase intention of people is tested by their green awareness, green perceived trust, green perceived value, green perceived risk and environmental responsibility. Multiple regression analysis is used to check the effects of green awareness, green perceived trust, green perceived risk, green perceived value and environmental responsibility on green purchase intention. Regression analysis showed that green perceived value is the top predictor of Pakistan adolescent’ green purchase intentions. The relationship between green awareness and green purchase intention is insignificant and weak. The relationship between green perceived trust and green perceived risk is not supported and relationship between green perceived trust and green perceived value is very stronger. This paper is a vital source of information for national and international marketers about what works and what does not work in appealing to the consumers of Pakistan.